The Ideological Origins of American Federalism. - LaCroix, Alison L. (Harvard University Press, 2010)
In this book, the author traces the history of American federal thought from its colonial beginnings in scattered provincial responses to British assertions of authority, to its emergence in the late eighteenth century as a normative theory of multilayered government. The core of this new federal ideology was a belief that multiple independent levels of government could legitimately exist within a single polity, and that such an arrangement was not a defect but a virtue.
Description based upon print version of record.
Keywords: Federal government -- United States -- History.; United States -- History -- Revolution, 1775-1783.; États-Unis -- Histoire -- 1775-1783 (Révolution); LAW / Government / Federal; Federal government; United States; Föderalismus; USA; Federalisme.; Politieke ideologie.; Verenigde Staten.; United States -- Politics and government.; United States of America.; Federalism.; Government.; Politics.; Revolutions.; History.; Federalism -- historia -- Förenta staterna.; 1775-1783; Geschichte.; History